Two women - Sahl, Ted (photographer):::Creator::::::::::::
Photograph shows two women posing by a bulletin board. The woman on the right is wearing a shiney top and the woman on the left is wearing a down vest. The bulletin board is almost completely filled with business cards. There are flyers posted on the wall around it and what may be small newspapers on a shelf below the flyers on the left. Part of a flyer on the left is legible. It reads: "You can get something for nothing but... do you want to keep it. Free VD screening. [Three illegible lines] 293-4525". Another flyer on the right reads: "Temesca[l] Gay Men Chorus. A concert. Wheelchair accessible".